2012
DOI: 10.1111/anae.12054
|View full text |Cite
|
Sign up to set email alerts
|

Organisation and planning of anaesthesia for emergency surgery

Abstract: SummaryPatients presenting for emergency surgery represent a category at high risk of complications, with substantial morbidity and mortality, whose management may be extremely challenging. In this first of two articles we consider the identification and evaluation of high risk emergency patients, the provision of critical care support, the management of sepsis, common postoperative complications and in‐theatre death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
(61 reference statements)
2
5
0
Order By: Relevance
“…We thank you for bringing this to our attention. We value Morris and Gray's in-depth article on the organisation and planning of anaesthesia for emergency surgery [1]. We agree with the limitations of the ASA scoring system set out within the article and have noted that compounding these factors is the frequent misquoting of the ASA 5 grade, both by clinicians and textbooks.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…We thank you for bringing this to our attention. We value Morris and Gray's in-depth article on the organisation and planning of anaesthesia for emergency surgery [1]. We agree with the limitations of the ASA scoring system set out within the article and have noted that compounding these factors is the frequent misquoting of the ASA 5 grade, both by clinicians and textbooks.…”
supporting
confidence: 65%
“…In our experience, the incorrect use of the pre-1987 definition also makes clinicians reluctant to classify patients as an ASA grade 5 due to perceived futility. We read with interest the editorial by Redfern and Harrop-Griffiths [1] and would like to make one small correction. In referring to our study that found more litigation against Canadian anesthesiologists over 65 compared with younger anaesthesiologists [2], Redfern and HarropGriffiths suggested this occurred especially for night and weekend work.…”
Section: Maddenmentioning
confidence: 99%
“…Spontaneously breathing patients in whom such monitoring would be most useful are those arriving in our emergency departments with trauma, an acute abdomen or bleeding, where the primary goals are rapid identification of risk and adequate resuscitation [14]. It is well known that emergency surgery is associated with a dramatically increase in mortality [15] and that the capacity for ICU admission, even though differing highly between countries [16], is often very limited [14].…”
mentioning
confidence: 99%
“…It is well known that emergency surgery is associated with a dramatically increase in mortality [15] and that the capacity for ICU admission, even though differing highly between countries [16], is often very limited [14]. A considerable number of these emergency patients are now being treated without the need for general anaesthesia, due to interventional methods that allow these procedures to be performed under sedation or regional anaesthesia [15,17].…”
mentioning
confidence: 99%
“…Not all reviews are aimed at informing which tubes to put down and which drugs to give; significant emphasis has been placed on both the organisational as well as clinical aspects of management. For example, in their eloquent article on the organisation and planning of anaesthesia for emergency surgery [2], Gray and Morris highlight the complex and challenging issues that surround this vital aspect of anaesthetic care; this they follow with a more practical review of clinical conduct for such anaesthesia [3]. in a detailed review of trauma management and its recent widespread developments, Lendrum and Lockey [4] inform us of the changes that are finally taking place in trauma management after decades of knowing that such care could be improved.…”
mentioning
confidence: 99%